Gas doping ratio effects on p-type hydrogenated nanocrystalline silicon thin films grown by hot-wire chemical vapor deposition - LUO, P; ZHOU, Z; CHAN, K; TANG, D; CUI, R; DOU, X (ELSEVIER SCIENCE BV, 2008)
Hydrogenated nanocrystalline silicon (nc-Si:H) grown by hot-wire chemical vapor deposition (HWCVD) has recently drawn significant attention in the area of thin-film large area optoelectronics due to possibility of high deposition rate. We report on the effects of diborane (B(2)H(6)) doping ratio on the microstructural and optoelectrical properties of the p-type nc-Si: H thin films grown by HWCVD at low substrate temperature of 200 degrees C and with high hydrogen dilution ratio of 98.8%. An attempt has been made to elucidate the boron doping mechanism of the p-type nc-Si:H thin films deposited by HWCVD and the correlation between the B(2)H(6) doping ratio, crystalline volume fraction, optical band gap and dark conductivity. (C) 2008 Elsevier B.V. All rights reserved.